Risks and incentives for gaming in electricity redispatch markets - Anna Pechan; Christine Brandstätt; Gert Brunekreeft; Martin Palovic (Constructor University Bremen, Bremen Energy Research (BER), 2023)
Market design for electricity often ignores network congestion initially and addresses it in a second, so-called 'redispatch' stage. For market participants, any two-stage design offers an opportunity to strategically optimize between the different market stages. The current debate is how to design a market-based redispatch to integrate new actors, in particular consumers, given increasing levels of congestion. Strategic bidding may occur if market players anticipate congestion in their region and manipulate bidding to exploit this congestion. In this paper, we pick up the current debate and study the precise incentives for gaming with respect to competitive conditions on the market with a formal model. We propose that depending on competitive conditions, the expected profits of gaming can be negative and link the range of negative expected gaming profits to a so-called reference bidder, reflecting competitive conditions in the market. We also discuss how several potential remedies can increase the risk of the gaming strategy and can thereby reduce the practical potential for gaming. With this paper, we provide the theoretical framework for authorities and empirical works to assess the potential of market-based as opposed to administrative redispatch.
Keywords: D21; D22; D43; L13; L94; 330; Electricity market; Market-based redispatch; Strategic behaviour; Inc-Dec gaming; congestion management